2017
DOI: 10.1103/physrevmaterials.1.054601
|View full text |Cite
|
Sign up to set email alerts
|

Unifying first-principles theoretical predictions and experimental measurements of size effects in thermal transport in SiGe alloys

Abstract: In this work, we demonstrate the correspondence between first principle calculations and experimental measurements of size effects on thermal transport in SiGe alloys. Transient thermal grating (TTG) is used to measure the effective thermal conductivity. The virtual crystal approximation under the density functional theory (DFT) framework combined with impurity scattering is used to determine the phonon properties for the exact alloy composition of the measured samples. With these properties, classical size ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…These directions are indicated by the manufacturer and confirmed by comparing the measured surface acoustic wave velocity to values computed for these surface directions using elastic theory [20,21]. In materials with phonon-dominated thermal transport, several authors have shown that thermal diffusivities measured using short-wavelength excitations, like those used in TGS, will be smaller than bulk diffusivities [4,11]. In brief, this reduction occurs due to the exclusion of long-wavelength ballistic phonons from the heat transport process.…”
Section: Methodsmentioning
confidence: 72%
See 4 more Smart Citations
“…These directions are indicated by the manufacturer and confirmed by comparing the measured surface acoustic wave velocity to values computed for these surface directions using elastic theory [20,21]. In materials with phonon-dominated thermal transport, several authors have shown that thermal diffusivities measured using short-wavelength excitations, like those used in TGS, will be smaller than bulk diffusivities [4,11]. In brief, this reduction occurs due to the exclusion of long-wavelength ballistic phonons from the heat transport process.…”
Section: Methodsmentioning
confidence: 72%
“…In brief, this reduction occurs due to the exclusion of long-wavelength ballistic phonons from the heat transport process. For SiGe alloys, Huberman et al have implemented a variational approach to solving the Boltzmann transport equation (BTE) for shortwavelength, 1D periodic excitations [11]. That method allows for the calculation of the expected value of the effective thermal diffusivity in pure Ge comfortably including the normal operating range of TGS test wavelengths of Λ = 1−10 µm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations